2021
DOI: 10.1111/nph.17585
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic‐stomatal coordination in tree seedlings: tight correlation across environments and ontogeny in Acer pseudoplatanus

Abstract: 1. Hydraulic conductance is recognized as a major determinant of gas exchange and productivity. However, whether this also applies to seedlings, a critically important stage for vegetation regeneration, has been largely unknown.2. We analyzed the hydraulic and stomatal conductance of leaves and shoots for 6-week-old Acer pseudoplatanus seedlings emerging in different lowland and treeline habitats and under glasshouse conditions, respectively, as well as on 9-, 15-and 18 week-old plants, and related findings to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 110 publications
(164 reference statements)
1
2
0
Order By: Relevance
“…In this study of both saplings and mature trees, leaf stomatal conductance had a strong positive correlation with K L (Figure 5a), suggesting that a decrease in leaf-specific apparent hydraulic conductance exercises a great influence on stomatal closure, reducing transpiration. This is in agreement with previous studies that documented the coordination of g s with plant hydraulic conductance [48,49]. Meanwhile, we found that the effect of K L on g s was different between saplings and mature trees via the slope rate of g s and K L (Figure 5a).…”
Section: The Effect Of Leaf Hydraulic Conductance On Stomatal Conduct...supporting
confidence: 93%
“…In this study of both saplings and mature trees, leaf stomatal conductance had a strong positive correlation with K L (Figure 5a), suggesting that a decrease in leaf-specific apparent hydraulic conductance exercises a great influence on stomatal closure, reducing transpiration. This is in agreement with previous studies that documented the coordination of g s with plant hydraulic conductance [48,49]. Meanwhile, we found that the effect of K L on g s was different between saplings and mature trees via the slope rate of g s and K L (Figure 5a).…”
Section: The Effect Of Leaf Hydraulic Conductance On Stomatal Conduct...supporting
confidence: 93%
“…However, growth performance was notably associated to a higher hydraulic efficiency in two of the three species, most likely through an increase in hydraulically-weighted vessel diameter (D h ), which was strongly and positively related to sapwood-specific hydraulic conductivity (K s ). In B. pendula and A. pseudoplatanus, two species with an isohydric water potential regulation strategy [45,58], and Kumar et al, unpublished, efficiency-related variables (e.g., D h and K s ) were associated with higher growth. This is consistent with earlier intra-and inter-specific studies reporting a close association of growth biomass increment to hydraulic efficiency rather than to other wood traits [14,34,37,59].…”
Section: Relationship Of Juvenile Growth With Hydraulic Safety and Ef...mentioning
confidence: 91%
“…It is also a transformer species that significantly changes its ecosystem's conditions (Richardson et al, 2000). Conversely, A. pseudoplatanus is also an invasive species, but it is also a critical silvicultural and ecological role in European forests (Beikircher et al, 2021). Besides these, Acer species as urban plants provide ecosystem services that range from carbon sequestration and heavy metal accumulation to shading urban surroundings and improving urban life quality.…”
Section: Introductionmentioning
confidence: 99%